Baseline Serum Interleukin-6 Levels Predict the Response of Patients with Advanced Non-small Cell Lung Cancer to PD-1/PD-L1 Inhibitors - Kang, Da Hyun; Park, Cheol-Kyu; Chung, Chaeuk; Oh, In-Jae; Kim, Young-Chul; Park, Dongil; Kim, Jinhyun; Kwon, Gye Cheol; Kwon, Insun; Sun, Pureum; Shin, Eui-Cheol; Lee, Jeong Eun (Immune network, 2020)
Although various studies on predictive markers in the use of PD-1/PD-L1 inhibitors are in progress, only PD-L1 expression levels in tumor tissues are currently used. In the present study, we investigated whether baseline serum levels of IL-6 can predict the treatment response of patients with advanced non-small cell lung cancer (NSCLC) treated with PD-1/PD-L1 inhibitors. In our cohort of 125 NSCLC patients, the objective response rate (ORR) and disease control rate (DCR) were significantly higher in those with low IL-6 (<13.1 pg/ml) than those with high IL-6 (ORR 33.9% vs. 11.1%, p=0.003; DCR 80.6% vs. 34.9%, p<0.001). The median progression-free survival was 6.3 months (95% confidence interval [CI], 3.9-8.7) in the low IL-6 group, significantly longer than in the high IL-6 group (1.9 months, 95% CI, 1.6-2.2, p<0.001). The median overall survival in the low IL-6 group was significantly longer than in the high IL-6 group (not reached vs. 7.4 months, 95% CI, 4.8-10.0). Thus, baseline serum IL-6 levels could be a potential biomarker for predicting the efficacy and survival benefit of PD-1/PD-L1 inhibitors in NSCLC.Although various studies on predictive markers in the use of PD-1/PD-L1 inhibitors are in progress, only PD-L1 expression levels in tumor tissues are currently used. In the present study, we investigated whether baseline serum levels of IL-6 can predict the treatment response of patients with advanced non-small cell lung cancer (NSCLC) treated with PD-1/PD-L1 inhibitors. In our cohort of 125 NSCLC patients, the objective response rate (ORR) and disease control rate (DCR) were significantly higher in those with low IL-6 (<13.1 pg/ml) than those with high IL-6 (ORR 33.9% vs. 11.1%, p=0.003; DCR 80.6% vs. 34.9%, p<0.001). The median progression-free survival was 6.3 months (95% confidence interval [CI], 3.9-8.7) in the low IL-6 group, significantly longer than in the high IL-6 group (1.9 months, 95% CI, 1.6-2.2, p<0.001). The median overall survival in the low IL-6 group was significantly longer than in the high IL-6 group (not reached vs. 7.4 months, 95% CI, 4.8-10.0). Thus, baseline serum IL-6 levels could be a potential biomarker for predicting the efficacy and survival benefit of PD-1/PD-L1 inhibitors in NSCLC.